1992
DOI: 10.1093/jaoac/75.5.780
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fourier Transform Infrared Analysis of Milk

Abstract: A Nicolet 510 Fourier transform infrared (FTIR) spectrometer was modified to perform IR milk analyses by incorporating a temperature-controlled 37 µm CaF2 flow cell and a homogenizer into the analytical system. The unit was evaluated for its ability to predict the chemical values of calibration milks, and its performance was compared with that of a commercial filter-based IR milk analyzer (Multispec MK1). Conventional dual-wavelength multiple regression methods and whole-spectrum multivariate analysis techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…The absorption spectra of wheat flour taken also show strong peaks in the same region represent presence of fat in flour. It has been reported that FTIR spectroscopy could be utilized as a quality control method for fat and moisture determination in butter and high-fat products (Van de Voort et al 1992). Similar results were also reported by Che-Man and Setiowaty (1999).…”
Section: Chemical Composition By Aacc Methods and Ft-ir Spectral Reprsupporting
confidence: 81%
“…The absorption spectra of wheat flour taken also show strong peaks in the same region represent presence of fat in flour. It has been reported that FTIR spectroscopy could be utilized as a quality control method for fat and moisture determination in butter and high-fat products (Van de Voort et al 1992). Similar results were also reported by Che-Man and Setiowaty (1999).…”
Section: Chemical Composition By Aacc Methods and Ft-ir Spectral Reprsupporting
confidence: 81%
“…In fact, Luinge et al (1993) evaluated 55 raw producer milks for calibration and validation performance, and concluded that there were no significant differences between reference chemistry minus FT MIR fat predictions using multivariate approaches and reference chemistry minus MIR fat predictions using a fixed-filter approach. Similar conclusions were made by van de Voort et al (1992). Thus, although multivariate calibration approaches would seem to have the potential to provide improved accuracy of fat testing by MIR, the reality is that no one has been able to demonstrate a significant performance improvement with multivariate approaches in comparison with a properly run fixed-filter approach.…”
Section: Improving the Mir Prediction Of Milk Fat Content By Adjustment Of Fat B Mir-predicted Values For A Change In Unsaturationsupporting
confidence: 59%
“…The absorption spectra of starter culture fermented sweet potato flour also show strong peaks in the same region, which indicates the presence of fat in flour. It has been reported that FTIR spectroscopy could be utilized as a quality control method for fat and moisture determination in butter and high-fat products (Van de Voort et al, 1992). Che-Man and Setiowaty (1999) and Rai et al (2013) also reported similar results.…”
Section: Discussionmentioning
confidence: 72%